Women’s empowerment in agriculture and dietary quality across the life course: Evidence from Bangladesh - Sraboni, Esha; Quisumbing, Agnes R. (International Food Policy Research Institute, 2018)
Using nationally representative survey data from rural Bangladesh, this paper examines the relationship between women’s empowerment in agriculture and indicators of individual dietary quality. Our findings suggest that women’s empowerment is associated with better dietary quality for individuals within the household, with varying effects across the life course. Women’s empowerment is associated with more diverse diets for children younger than five years, but empowerment measures are not consistently associated with increases in nutrient intake for this age group. Women’s empowerment is positively and significantly associated with adult men’s and women’s dietary diversity and nutrient intakes. Different empowerment domains may have different impacts on nutrition, but other characteristics, such as maternal schooling and household socioeconomic status, may play a more important role for younger children. The importance of maternal education in the dietary quality of young children, and the relatively greater importance of women’s empowerment for older children and adults, imply that policies designed to empower women and improve nutritional status should be informed by knowledge of which specific domains of women’s empowerment matter for particular nutritional outcomes at specific stages of the life course.